Hydrogen refuelling station with integrated metal hydride compressor: Layout features and experience of three-year operation. (14th February 2020) - Lototskyy, Mykhaylo; Davids, Moegamat Wafeeq; Swanepoel, Dana; Louw, Gerhard; Klochko, Yevgeniy; Smith, Fahmida; Haji, Fatema; Tolj, Ivan; Chidziva, Stanford; Pasupathi, Sivakumar; Linkov, Vladimir
Abstract: Hydrogen compression is a main contributor in the capital and operation costs of the H2 refuelling infrastructure. The use of metal hydrides (MH) for thermally-driven H2 compression can provide efficient solution to mitigate this challenge. MH compressors are particularly promising for industrial customers who possess necessary infrastructure including pipeline H2, sources of low-grade heat, etc. Here we present the details about layout of the H2 refuelling station and its operation at Impala Platinum refineries in Springs, South Africa, since its start-up in September 2015. The station provides H2 dispensing at the pressure up to 185 bar and uses pipeline H2 (P = 50–60 bar) available at the customer site. H2 compression to P = 200 bar with productivity up to 13 Nm 3 /h is provided by the integrated 1-stage MH H2 compressor which uses steam (T∼140 °C) for the heating and circulating water (T∼20 °C) for the cooling; both steam and water are also available from the customer infrastructure. The station also includes H2 dispenser, buffer tank (standard gas cylinder pack), and control block on the basis of Siemens Program Logic Controller (PLC) which provides fully automated system operation. Switching H2 and steam/water flows is carried out with the help of remotely controlled, pneumatically actuated valves and auxiliary check valves. Additionally, at P = 200 bar the control block switches the system into standby mode when MH compression modules are cooled down and their gas manifolds are connected to the H2 supply line. The H2 dispensing is independent on the compressor operation and takes from 6 to 15 min. The refuelling station complies with South African safety regulations for operation in a fire and explosion hazardous environment. Graphical abstract: Image 1 Highlights: Hydrogen refuelling station with integrated metal hydride compressor. Utilises services including low pressure H2 and low-grade steam available for industrial customers. Dispensing capacity from 13 to 28 kg H2/day at a pressure of 185 bar. Lower capital and operational costs as compared to high pressure stations available on the market. In uninterrupted operation at Impala Platinum Refineries (South Africa) since September 2015.